Consumption of Impressions: A New Approach to the Formation of Tourist Attractiveness of Russian Territories - FROLOVA, Elena V.; ROGACH, Olga V.; RYABOVA, Tatyana M.; MEDVEDEVA, Natalia V. (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.v11.6(46).04, 2020)
The article attaches the results of the study of the processes of formation of the tourist attractiveness of the Russian territories in the focus of studying the specificity of the consumption of tourist impressions. The leading survey method was a questionnaire survey of residents of Moscow and the Moscow region (N = 537 people). A modern tourist, distinguished by high speed of movement, the desire to cover the maximum number of sightseeing points that are required for viewing, more and more often forms his perception of the tourist attractiveness of the territories through the consumption of impressions: the life of others, traditions, culture, places and archetypes. The authors consider new trends in the development of the tourism industry, the transformation of patterns of tourist behavior. The key components of the consumption of impressions have been identified, namely: visualization and the possibility of replicating impressions, the acquisition of sensory experience by the tourist, involvement in tourist practices, the uniqueness and authenticity of the tourist product. Among the respondents satisfied with the possibility of photographing tourist attractions, a higher proportion of respondents who received a positive impression of the trip was recorded. The fixation of impressions is considered by most tourists as an opportunity for self-presentation of personal achievements. The importance of visualization of impressions actualizes such practices of forming the tourist attractiveness of Russian territories, such as organizing green pedestrian zones, marking tourist routes with photo and video points, embedding the natural landscape in urban space. The study found that the formation of tourist attractiveness of the territories is centered not so much around meeting the cultural and educational needs of the tourist as around wanting to get aesthetic satisfaction from the trip, emotional involvement in the contemplation of tourist attraction objects, the possibility of replicating their impressions in social networks. A new trend in shaping the tourist attractiveness of Russian territories is becoming an orientation towards receiving unique tourist services and exclusive impressions (gastronomic experience, interactive forms of leisure). The study showed that traditional dysfunctions in terms of the development of domestic tourism (typical appearance of cities, unification of the range of tourist services, low level of infrastructure support) can be compensated by implementing flagship projects for getting impressions, creating unique tourist destinations, promoting them in social networks, developing interactive travel practices, the development of exclusive and authentic tourist products.